Superelasticity behaviour of NiTi actuator at different strain rates - Karunakaran, Sivasanghari; Abang Abdul Majid, Dayang Laila; Imran, Husam Yahya (The Aeronautical and Astronautical Society of the Republic of China, 2024)
A small compact shape memory alloy actuator wire can generate large forces repeatedly and have found significant potential in aerospace components. Thermomechanical characterization of actuator wire under tensile loading can cause extreme sensitivity of the SMA material response, thus affect the performances of SMA. Previously, most research were focused on the effect of compositions and manufacturing parameters on the performances of SMA. Nonetheless, several factors like strain rate, activation temperature and activation time can potentially affect the performance of SMA. This experimental study investigated the strain rate effect on the superelasticity behaviour of the NiTi actuator with diameter of 0.31mm at a constant activation temperature of 70 °C. Instron 3366 Universal Testing Machine (UTS) with a 5 kN load cell, which was mounted with heat control chamber, was used to apply uniaxial tension to the NiTi wire. The test underwent loading and unloading process at three different strain rates of 0.04 mm/min, 0.2 mm/min and 1.0 mm/min, respectively. The results showed that the phase transformation stresses and stress during the transformation phase increased with increasing strain rate. Hysteresis loop increased gradually with strain rate but showed significant reduction at higher strain rate. Overall, this study successfully highlighted the potential influences of strain rate on the possible use of SMA actuator in large force generation applications.